FEATURES OF THE TERMINOLOGY OF THE ENGLISH LANGUAGE IN THE FIELD OF ELECTRIC POWER INDUSTRY (Intent Research Scientific Journal, 2023)
The authors of this article consider the peculiarities of terminology and term formation in the electric power field of the English language. It is noted that due to the ongoing process of globalization of the energy field, as well as the expansion of the industry towards the development of unconventional energy sources, improving the reliability of power systems, increasing the volume of data of various measurements, the process of term formation is actively continuing and the terminology of national languages needs to be harmonized. The authors have identified such features of terminology and term formation as metaphor terms, synonyms-Latinisms and rules for the formation of their plural, as well as composite terms. It is noted that for constructive communication in this area, energy engineers should pay attention to these aspects.